Pengaruh Kualitas Pelayanan Terhadap Minat Mitra Koperasi Syariah Yang Dimediasi Oleh Kepuasan - Muhammad Anwar Rifa'i; Marfudin Marfudin; Jasman Jasman; Mastur Mastur (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
This research was conducted to confirm and unravel the phenomenon of the development of the Asy-Syafi’iyah cooperative which is considered quite rapid in its development in terms of factors that affect the interest of Asy-Syafi’iyah cooperative partners. The factors studied are service quality and satisfaction. The analysis used in this study was path analysis with a structural equation modeling (SEM) model with a research sample of Al-Yanisi Cooperative partners totaling 101 respondents. The results of the study explained that first, the quality of service directly affects the interest in becoming a member of the Asy-Syafi’iyah Tugumulyo Cooperative positively and significantly, which means that the better the quality of service, the interest of partners to become members of the cooperative will also increase. Both service qualities indirectly affect the interest in becoming a member of the Asy-Syafi’iyah Tugumulyo Cooperative through positive and significant service satisfaction, which means that the better the quality of service, it will increase partner’s satisfaction, and it will increase the interest of partners to become cooperative members.